F(x)=2x^2-x-6
Factoring:
f(x)=2(2x^2-x-6)/2=(2^2x^2-2x-12)/2=[(2x)^2-(2x)-12]/2
f(x)=(2x-4)(2x+3)/2=(2x/2-4/2)(2x+3)→f(x)=(x-2)(2x+3)
g(x)=x^2-4
Factoring
g(x)=[sqrt(x^2)-sqrt(4)][sqrt(x^2)+sqrt(4)]
g(x)=(x-2)(x+2)
f(x)/g(x)=[(x-2)(2x+3)] / [(x-2)(x+2)
Simplifying:
f(x)/g(x)=(2x+3)/(x+2)
Answer: Third Option (2x+3)/(x+2)
Answer:
c = -4
Step-by-step explanation:
16 = 4 - 3c
subtract 4 from each side
16-4 = 4-4 - 3c
12 = -3c
Divide each side by -3
12/-3 = -3c/-3
-4 =c
Answer:
The simplest (and most commonly used) area calculations are for squares and rectangles. To find the area of a rectangle, multiply its height by its width. For a square, you only need to find the length of one of the sides (as each side is the same length) and then multiply this by itself to find the area.
Answer:
Step-by-step explanation:
Mean = ∑x/ N
91 = ∑x / 150
∑x = 150 * 91 = 13650
x= 6825 and y = 6825
Answer:
b.
Step-by-step explanation:
rise step-chickens!!!!